In Silico Identification of Housekeeping Genes by Expressed Sequence Tags and Assessment of Short Tandem Repeats in Their Promoters - Mahboobeh Ramezani; Bita Javan; Mohammad Hasan Jafari; Arsham Banisadr; Mahdieh pourafshar; seyedeh Sara Raeissadati; Pardis Mokhtary; Mohammad Arefi; Azizeh Karimian; Morteza Oladnabi (Journal of Clinical and Basic Research, 2021)
Background and objectives: In gene expression studies, to validate and obtain reliable results, normalization of qRT-PCR data by housekeeping genes (HKGs) is required. However, the expression level of these genes may vary in tissues or cells and may change under certain circumstances. Thus, selection of HKGs is critical for gene expression studies. For this purpose, we analyzed expression of protein-coding genes by expressed sequence tags (ESTs) and short tandem repeat (STR) to select suitable HKGs. Methods: The EST profile of 17242 protein-coding genes was extracted from the UniGene database. Log2 (TPM + 2) scale was used to normalize EST counts across 16 normal and tumor tissues. Selection of HKGs was limited to genes expressed in developmental stages as well as  in normal and tumor tissues. Then, the genes with no expression change between the normal and tumor tissues were selected. Finally, the STRs and the gene ontology analysis of candidate genes were performed. Results: We found that 93 genes had no expression change between the normal and tumor tissues. The STRs analysis showed that GCGCGC repeats had the highest frequency in candidate gene promoters. Conclusion:  We introduced a new set of genes as potential HKGs, some of which can be used for a particular tissue. However, further investigations are required to confirm our findings.